1973
DOI: 10.1530/jrf.0.0320141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyproterone Acetate on the Adenohypophysial Cells of Male Rats

Abstract: Cyproterone acetate, a synthetic antiandrogenic steroid, caused a marked reduction in the weights of the accessory sex glands when given to male rats. The compound also affected the anterior lobe of the pituitary causing a decrease in the numbers of growth-hormone\x=req-\ producing cells. Cyproterone acetate did not inhibit spermatogenesis and the Leydig cells were normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Only the progestational effect increases aggression. Opposed to this as aggression-reducing components are the antiandrogenic effect (Donald et al -1976), the androgen-dependent aggression-inducing pheromones (Nowel1et al -1969), the antigonadotropic effect (Donald et al -1976) and the decrease of ACTH (Neumann -1977) and STH (Laksman et al -1973). Gonadotropins, STH and ACTH can increase aggression (Matte, to be published).…”
Section: Discussionmentioning
confidence: 99%
“…Only the progestational effect increases aggression. Opposed to this as aggression-reducing components are the antiandrogenic effect (Donald et al -1976), the androgen-dependent aggression-inducing pheromones (Nowel1et al -1969), the antigonadotropic effect (Donald et al -1976) and the decrease of ACTH (Neumann -1977) and STH (Laksman et al -1973). Gonadotropins, STH and ACTH can increase aggression (Matte, to be published).…”
Section: Discussionmentioning
confidence: 99%
“…The PAS-Orange G-methyl blue staining technique showed that PAS-purple cells were more numerous than PAS-red cells. The former have been identified as delta-basiphils (FSH-cells) in both rats (Lakshman & Isaac, 1973) and gerbils (Kaul & Ramaswami, 1973). Treatment with a-chlorohydrin brought about remarkable changes in the delta-basiphils.…”
mentioning
confidence: 99%